Interest Rates and Environmental Pollution - Rashid, Muhammad; Sharma, Basu (Journal of Comparative International Management)

(untitled) (None, 2008)
While there is a growing body of theoretical and empirical literature examining the effects of such macroeconomic variables as growth of gross domestic product, international trade, incomes distribution and foreign direct investment on environmental pollution, one dimension lacking in the current literature is the impact of interest rates on pollution. If interest rates decline (rise), firms with capital-intensive technologies will invest more (less) relative to firms with labor-intensive technologies. Additionally, according to Rybczynski theorem, in a situation of full employment and a competitive labour market, labor will shift towards the capital-intensive industries from labor –intensive ones. Consequently, the products of capital-intensive industries will expand (contract) relative to products of labor-intensive industries. The capital-intensive industries are generally deemed to be polluting while labor-intensive industries are perceived to be non-polluting. This suggests that the movements of interest rates may have a discernible environmental outcome which has been neglected in the literature so far. To begin to fill this gap, in this paper, we construct a two-good and two-factor closed economy model to show the impact of interest rates on environmental pollution in a formal way. The theoretical results of the paper are illustrated numerically.